The sustainability debate : policies, gender and the media - Topić, Martina; Lodorfos, George (Emerald Publishing Limited, 2021)
'The Sustainability Debate' is the result of a collaboration between academics and members of the Retail Institute predominantly working in retail and packaging industries. It responds to practitioners' frustration with consumers' emotionality and lack of knowledge around sustainability issues, problems often fostered by the media. This fourteenth volume of 'Critical Studies on Corporate Responsibility, Governance and Sustainability' thus puts together a debate that goes beyond the rhetoric of environmental protection and looks at sustainability from several angles. The book is predominantly focused on human and social sustainability and this focus is carried into sections that discuss sustainable policies, media and gender. This volume ultimately moves away from merely discussing environmental protection and shifts to the effect sustainable policies have on people and society. With a scope expanded to include human and social sustainability as well as economic sustainability, this book's original contribution is that is sees sustainability as a dynamic and complex system of human, social and environmental aspects.- Resumé vydavatelé
Includes index.
Keywords: udržitelný rozvoj; společenská odpovědnost firem; sustainable development; corporate social responsibility; elektronické knihy; sborníky; electronic books; papers of several authors